Hepatic Autophagy Deficiency Compromises FXR Functionality and Causes Cholestatic Injury - Khambu, Bilon (Hepatology, 2019)
Autophagy is important for hepatic homeostasis, nutrient regeneration and organelle quality control. We investigated the mechanisms by which liver injury occurred in the absence of autophagy function. We found that mice deficient in autophagy due to the lack of Atg7 or Atg5, key autophagy-related genes, manifested intracellular cholestasis with increased levels of serum bile acids, a higher ratio of TMCA/TCA in the bile, increased hepatic bile acid load, abnormal bile canaliculi and altered expression of hepatic transporters. In determining the underlying mechanism, we found that autophagy sustained and promoted the basal and upregulated expression of Fxr in the fed and starved conditions, respectively. Consequently, expression of Fxr and its downstream genes, particularly Bsep, and the binding of FXR to the promoter regions of these genes, were suppressed in autophagy-deficient livers. In addition, co-deletion of Nrf2 in autophagy deficiency status reversed the FXR suppression. Furthermore, the cholestatic injury of autophagy-deficient livers was reversed by enhancement of FXR activity or expression, or by Nrf2 deletion. CONCLUSIONS: Together with earlier reports that FXR can suppress autophagy our new findings indicate that autophagy and FXR form a novel regulatory loop and deficiency of autophagy causes abnormal FXR functionality, leading to the development of intracellular cholestasis and liver injury.